Outcomes of Durable Mechanical Circulatory Support in Myocarditis: Analysis of the International Society for Heart and Lung Transplantation Registry for Mechanically Assisted Circulatory Support Registry. Issue 2 (22nd March 2021) - Al-Kindi, Sadeer G.; Xie, Rongbing; Kirklin, James K.; Cowger, Jennifer; Oliveira, Guilherme H.; Krabatsch, Thomas; Nakatani, Takeshi; Schueler, Stephan; Leet, Angeline; Golstein, Daniel; Elamm, Chantal A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Myocarditis can be refractory to medical therapy and require durable mechanical circulatory support (MCS). The characteristics and outcomes of these patients are not known. We identified all patients with clinically-diagnosed or pathology-proven myocarditis who underwent mechanical circulatory support in the International Society for Heart and Lung Transplantation Registry for Mechanically Assisted Circulatory Support registry (2013–2016). The characteristics and outcomes of these patients were compared to those of patients with nonischemic cardiomyopathy (NICM). Out of 14, 062 patients in the registry, 180 (1.2%) had myocarditis and 6, 602 (46.9%) had NICM. Among patients with myocarditis, duration of heart failure was <1 month in 22%, 1–12 months in 22.6%, and >1 year in 55.4%. Compared with NICM, patients with myocarditis were younger (45 vs. 52 years, P < 0.001) and were more often implanted with Interagency Registry for Mechanically Assisted Circulatory Support profile 1 (30% vs. 15%, P < 0.001). Biventricular mechanical support (biventricular ventricular assist device [BIVAD] or total artificial heart) was implanted more frequently in myocarditis (18% vs. 6.7%, P < 0.001). Overall postimplant survival was not different between myocarditis and NICM (left ventricular assist device: P = 0.27, BIVAD: P = 0.50). The proportion of myocarditis patients that have recovered by 12 months postimplant was significantly higher in myocarditis compared to that of NICM (5% vs. 1.7%, P = 0.0003). Adverse events (bleeding, infection, and neurologic dysfunction) were all lower in the myocarditis than NICM. In conclusion, although myocarditis patients who receive durable MCS are sicker preoperatively with higher needs for biventricular MCS, their overall MCS survival is noninferior to NICM. Patients who received MCS for myocarditis are more likely than NICM to have MCS explanted due to recovery, however, the absolute rates of recovery were low.